THE ANALYSIS OF POLITENESS STRATEGEY USED BY THE MAIN CHARACTER OF NOVEL “THE SUN ALSO RISES” - Widyastuti Widyastuti (Journal of Pragmatics Research, 2019)
The objective of this research is to explore politeness strategies used by the main characters in novel “The Sun also Rises”. The analysis is based on the utterances of the main characters. The researcher analyzed the utterances in order to find out the types of politeness strategies used by the main characters. In this research, the researcher used descriptive qualitative by using documentation and observation method of collecting data from the novel. From the analysis of the novel, showed that the main character in The Sun also rises applied the types of politeness strategies, namely bald on record, positive politeness, negative politeness and off record. The main characters also revealed the factors affecting the characters’ politeness in speaking, namely language style, register and domain, slang and solidarity, language and gender in their conversation.  Keywords: Politeness Strategy, Character, The Sun Also Rises